A midnight pastry shop called Hwawoldang : a novel - Lee, Onhwa (William Morrow, 2026)
"For readers of Before the Coffee Gets Cold, The Dallergut Dream Department Store, and The Midnight Library, a sweetly magical and uplifting novel about a young woman who inherits an enchanted bakery that spirits visit on their last stop before the afterlife"-- Provided by publisher.